Consumer Return Policies in Omnichannel Operations - Nageswaran, Leela; Cho, Soo-Haeng; Scheller-Wolf, Alan (Management Science, 2020)
We study the pricing and return policy decisions of an omnichannel retailer serving customers who differ in how they realize their uncertain valuation for a product—by inspecting in store before purchase or by purchasing online and possibly returning misfit products. Customers may return misfit products either to stores for a full refund or online as per the firm’s return policy. We model prices to be identical across channels, allow crosschannel returns, and endogenize customers’ purchase and return decisions, capturing typical features of an omnichannel setting. Our analysis helps explain why some omnichannel firms choose full refunds, whereas others charge a fee for online returns. We find that omnichannel firms with good salvage partners for online returns (e.g., Nordstrom) as well as those with more store-based customers (e.g., Macy’s) should offer full refunds. Similarly, firms are incentivized to offer full refunds for products that customers are more likely to inspect in store (e.g., Express for footwear). In contrast, firms with a significant store network and better in-store salvage opportunities (e.g., J.C. Penney) might be better off charging a fee for online returns in order to nudge customers to return in store. Finally, an omnichannel firm should be cautious both in making the return process more convenient and in improving accessibility to its stores, because these seemingly beneficial policies, if combined with a partial-refund policy, could undermine the firm’s overall profit. This paper was accepted by Vishal Gaur, operations management.